Political Manifestation of Economic Backwardness In Assam - Dr. JOYEETA AHMAD (International journal of economic perspectives, 2022)
Since Aristotle social philosophers have often contemplated that economic inequality is an intrinsic cause of political violence and unrest. A huge chunk of literature holds the view that the way wealth is dispersed in the society is the sole indicator of the extent of inequality. De Tocqueville also of the view that all revolutions that have changed the destiny of nations were meant to either consolidate or ameliorate social inequality. Karl Marx was also of the view that political violence has its roots in the unequal distribution of wealth. He had held that private property results in the unequal distribution of social wealth which impoverishes the proletariat and makes them politically conscious. This consciousness in turn leads to revolution.